Assessing the application of International Accounting Standards for small and medium-sized Enterprises in Oman - Mukhtar, Ashraf Abdullateef Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to investigate the possibility of applying international accounting standards for small and medium enterprises in Oman, and to survey the problems and difficulties facing the application of these standards. The problem of this study centered around the main question about the suitability of international accounting standards to be applied for small and medium-sized enterprises in Al Dakhiliyah Governorate in Oman?, Several sub-questions emerged from it. To achieve the objectives of this study and to solve its problem, a questionnaire was distributed to a random sample of 100 small and medium enterprises operating in Al Dakhiliyah Governorate in the Oman. The analytical descriptive approach was followed in data collection and analysis, as (SPSS) version 11.5 used to analyze the data. The study reached several results, the most important of which is: There is a good level of familiarity with international accounting standards for small and medium-sized enterprises, but the percentage of their use is very weak. The most important obstacles to the application of international standards are the lack of material aids to apply them, as these standards are not commensurate with the capabilities of the weak small and medium-sized enterprise. The study recommended the necessity of qualifying and training accountants in small and medium-sized enterprises about international standards, and that external auditors and consultants for this type of institute should recommend and encourage permanently adopting international standards and highlighting their advantages in their reports.
Keywords: International Accounting Standards; Small and Medium Enterprises; Dakhiliyah Governorate in Oman